2015
DOI: 10.1002/jbmr.2465
|View full text |Cite
|
Sign up to set email alerts
|

Deficits in Trabecular Bone Microarchitecture in Young Women With Type 1 Diabetes Mellitus

Abstract: The pathophysiological mechanism of increased fractures in young adults with type 1 diabetes mellitus (T1DM) is unclear. We conducted a case-control study of trabecular bone microarchitecture and vertebral marrow adiposity in young women with T1DM. Thirty women with T1DM with a median age (range) age of 22.0 years (16.9, 36.1) attending one outpatient clinic with a median age at diagnosis of 9.7 years (0.46, 14.8) were compared with 28 age-matched healthy women who acted as controls. Measurements included MRI-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 53 publications
4
74
4
1
Order By: Relevance
“…In some human studies, bone resorption in T1DM is either decreased or unaltered and does not explain the low BMD observed in this disease (80). In children and young adults, T1DM patients had lower PINP and CTX levels compared to controls (67,81). However enzymatic cross-linking of collagen is reduced in diabetes (82).…”
Section: Bone Turnovermentioning
confidence: 93%
See 1 more Smart Citation
“…In some human studies, bone resorption in T1DM is either decreased or unaltered and does not explain the low BMD observed in this disease (80). In children and young adults, T1DM patients had lower PINP and CTX levels compared to controls (67,81). However enzymatic cross-linking of collagen is reduced in diabetes (82).…”
Section: Bone Turnovermentioning
confidence: 93%
“…These data suggest that MVD may be an independent risk factor of fractures. By magnetic resonance imaging (MRI), Adbalrahaman confirmed trabecular deficits with reduced bone volume and trabecular number at the proximal tibia of young adults with childhood onset of T1DM, as well as increased medullary fat in the vertebrae (67).…”
Section: Bone Size and Microstructurementioning
confidence: 93%
“…The decrease was especially prominent in patients with signs of microangiopathy (expressed as retinopathy) (38). However, this may reflect some of the growth issues related to T1D in young persons.…”
Section: Bone Density and Microarchitecturementioning
confidence: 93%
“…A recent study using MRI (38) in young women with T1D (median age 22 years, median age at diagnosis 9.7 years) reported reduced bone volume and increased trabecular spacing. The decrease was especially prominent in patients with signs of microangiopathy (expressed as retinopathy) (38).…”
Section: Bone Density and Microarchitecturementioning
confidence: 99%
“…Clinically, in one small study of girls ages 12-15 with T1DM, serum IGF1 concentrations positively correlated with estimates of bone strength as measured by peripheral quantitative computed tomography 75 . Intriguingly, 2 recent studies of skeletal microarchitecture in adults with childhood onset T1DM have demonstrated decreased trabecular bone density at the distal radius and tibia 76,77 ; in both, effects on bone density were limited to those subjects who had clinical evidence of diabetic microvascular disease. These findings again point to the intimate relationship of compromised growth and bone accrual with classic microvascular disease.…”
Section: Clinical Implications Of Impaired Growthmentioning
confidence: 99%